KAJIAN EKONOMI USAHATANI KENTANG DI KECAMATAN SUKAPURA KABUPATEN PROBOLINGGO - Ana Arifatus Sa’diyah; Rikawanto Eko Muljawan (BUANA SAINS, 2011)
Probolinggo Regency especially Sukapura is one of potato production center area since this area is very suitable for potato plants. Some problems are always faced by the farmers in that area was restrictiveness of capital such as wide of land, seeds, fertilizer, medicines, and employees. This research aimed to find out the productivity of potato, factors affecting potato production, income of farmer business entity of potato, and efficiency of product ion cost at farmer business entity of potato. The research method used was descriptive and correlation method, by determining the area purposively (purposive method). The method used to take the example was Disproportionate Stratified Random Sampling Method by stratum of area’s height. The data collection was done by using primary and secondary data. The data analysis used covered: (1) analysis of productivity index to know the productivity of potato, (2) analysis of production function of Cobb-Douglas to know the factors affecting the potato productivity, (3) analysis of income to know the profit of potato farmers, and (4) analysis of R/C ratio to know the efficiency of production cost at farmer business entity of potato. The research result done showed that: (1) the potato productivity was 12,797.78 kg/ha; (2) the potato productivity was affected by the wide of land, seeds, fertilizer, medicines, employees, and height of location, (3) the farmer business entity of potato was profitable, and (4) the use of production cost at farmer business entity of potato was efficient (R/C = 1,72)